Tidal propagation in the Lower Fraser River, British Columbia, Canada. (5th January 2022) - Wu, Yongsheng; Hannah, Charles; Matte, Pascal; O'Flaherty-Sproul, Mitchell; Mo, Ruping; Wang, Xiaoyi; MacAulay, Phillip
Abstract: We investigated the tidal propagation in the Lower Fraser River (LFR) in British Columbia, Canada using observed water elevations, river discharge, and a hydrodynamic model. The observed water elevations and discharge are analyzed using a tidal analysis package called NS_Tide. The results indicate that the amplitudes of the two principal tides (lunar semidiurnal, M2, and luni-solar diurnal, K1 ) decrease from the river mouth to the upstream. The amplitudes in the high flow season (spring and summer) are lower than those in the low flow season (fall and winter). The amplitudes of the overtides and compound tides amplify from the downstream to the upstream in the low flow season; however, in the high flow season, the amplitudes only amplify in the lower part (0–35 km from the river mouth) and then decrease in the upper part (60–78 km from the river mouth). The temporal variation of tidal amplitudes are strongly correlated to the river discharge. Using the model results in 2013, we analyzed the momentum balance in the river channel and examined the significance of the Pitt River and Pitt Lake system. The momentum balance in the river channel is dominated by the balance between the pressure gradient and the bottom friction. The river-tide interaction plays an important role in the friction term in the lower part of the river channel, while the river flow explains most of the variability moving upstream. The system of the Pitt River and Pitt Lake is important for the tidal propagation in the river channel. Modelling tides without including this system systematically leads to significant inaccuracies of the tides in the river channel of the LFR. Highlights: Tides in the lower Fraser River are temporally and spatially variable. Tides are damped due to the river discharge. The river-tide interaction plays an important role in the bottom friction term in the lower part of the river channel. The system of the Pitt River and Pitt Lake is important for the tidal propagation in the river channel.